Continuous Dopaminergic Stimulation in Parkinson’s Disease 1988
DOI: 10.1007/978-3-7091-8954-2_13
|View full text |Cite
|
Sign up to set email alerts
|

Continuous intracerebroventricular infusion of dopamine and dopamine agonists through a totally implanted drug delivery system in animal models of Parkinson’s disease

Abstract: We studied the effect of intracerebroventricular infusion of dopamine and dopamine agonists in rat and pnmate models of Parkinson's disease as an experimental approach to the treatment of levodopa-induced fluctuations. The infusion of dopamine, lisuride, and pergolide into the ventricle ipsilateral to the lesion, by bhydroxydopamine, of the nigrostriatal pathway induced a contralateral rotation which was maximal 24-48 h after infusion and whose intensity progressively decreased over the period of 1 week. PHISp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
(9 reference statements)
1
6
0
Order By: Relevance
“…Second, microglia-derived factors were detected only after the occurrence of substantial neuronal damage. Third, consistent with other reports (37)(38)(39), pargyline completely blocked the damage of dopaminergic neurons induced by MPTP. More importantly, associated with the attenuation of MPTP neurotoxicity, pargyline abolished the microglial activation (this study).…”
Section: Discussionsupporting
confidence: 92%
“…Second, microglia-derived factors were detected only after the occurrence of substantial neuronal damage. Third, consistent with other reports (37)(38)(39), pargyline completely blocked the damage of dopaminergic neurons induced by MPTP. More importantly, associated with the attenuation of MPTP neurotoxicity, pargyline abolished the microglial activation (this study).…”
Section: Discussionsupporting
confidence: 92%
“…Local infusion has also been used in treatment for models of other neurological disorders. Intraventricular infusion of dopamine agonists has been used in animal models of Parkinson's syndrome (8). Dexamethasone has been delivered focally by osmotic pump to regions of brain tumors in rabbits (9).…”
Section: Discussionmentioning
confidence: 99%
“…All animals treated with reserpine exhibited behavioral features associated with an acute loss of dopamine. Although striatal dopamine depletion was not measured in the present study, previous studies have reported that reserpine treatment reduces dopamine levels to 5% of that of nonreserpinised animals 47, 48. Reserpine treatment causes a reversible depletion of vesicular dopamine and does not result in actual loss of dopaminergic neurons; this mechanism makes it a useful acute model for studying the effects of acute dopamine depletion and the regulation of receptors in the basal ganglia circuit by dopamine.…”
Section: Discussionmentioning
confidence: 59%